PENGEMBANGAN PEMBELAJARAN IPS TERPADU DI SMP NEGERI 8 MARTAPURA KABUPATEN BANJAR - Fitri Jamilah (JURNAL SOCIUS, 2017)
Social studies in junior high school implemented with integrated learning model, is one model of curriculum implementation are recommended to be applied at all levels of education, from elementary school (SD / MI) up to high school (SMA / MA). Currently the schools in the district of Banjar, especially junior high school teachers generally available Social Science consists of teachers, teachers' disciplines such as Geography, Sociology/Anthropology, Economics, and History. Teachers with that background would be difficult to adapt to the integration of the discipline of the social sciences, for example, teachers who have a background in geography does not have an optimal capacity in the economy and history, and also teachers set of economics does not have the ability to optimally on the history and geography , In connection with the need for research and innovation by teachers IPS against efforts to develop integrated social studies lesson for the learning process IPS on a junior high school in Banjar Regency, especially SMP Negeri 8 Martapura can take place effectively and efisiean in achieving the goal of learning itself.This study was designed with the Development Research (Research and Development) phase Define and Design that aims to develop learning Integrated Social Science in SMP Negeri 8 Martapura using a model-based approach major potential, a model-based approach problems, and a model-based approach topics. The technique of collecting data using interviews and documentation.The results showed the implementation of the Integrated Social Learning in SMPN 8 Martapura still not been implemented, learning today is still separately. The main limiting factor is the limited ability of teachers to develop learning devices Integrated IPS. Researchers developed a learning device Integrated IPS, the Define phase, carried out an analysis of competency standards and basic competencies has the potential to be combined, then all competency standards and basic competencies are integrated through themes. then made the development of the network competency standards and basic competencies. In the Design phase, to design the syllabus and lesson plan (RPP) Integrated Social science.Keywords: Learning Development, Integrated Social SciencePembelajaran IPS di SMP dilaksanakan dengan model pembelajaran terpadu, merupakan satu model implementasi kurikulum yang dianjurkan untuk diaplikasikan pada semua jenjang pendidikan, mulai dari tingkat Sekolah Dasar (SD/MI) sampai dengan Sekolah Menengah Atas (SMA/MA). Saat ini pada sekolah-sekolah di Kabupaten Banjar, khususnya jenjang SMP umumnya guru-guru IPS yang tersedia terdiri atas guru-guru disiplin ilmu seperti guru Geografi, Sosiologi/Antropologi, Ekonomi, dan Sejarah. Guru dengan latar belakang tersebut tentunya sulit untuk beradaptasi ke dalam pengintegrasian disiplin ilmu-ilmu sosial. Sehubungan dengan itu perlu adanya kajian dan inovasi oleh para guru IPS terhadap upaya pengembangan pembelajaran IPS terpadu.Penelitian ini dirancang dengan Penelitian Pengembangan (Research and Development) model 4-D tahap Define dan Design yang bertujuan mengembangkan pembelajaran IPS Terpadu di SMP Negeri 8 Martapura dengan menggunakan model pendekatan berdasarkan potensi utama, model pendekatan berdasarkan permasalahan, dan model pendekatan berdasarkan Topik. Teknik pengumpulan data menggunakan dokumentasi dan wawancara.Hasil penelitian menunjukan pelaksanaan Pembelajaran IPS Terpadu di SMPN 8 Martapura masih belum dilaksanakan, pembelajaran selama ini masih secara terpisah. Faktor penghambat utama adalah keterbatasan kemampuan guru mengembangkan perangkat pembelajaran IPS Terpadu. Peneliti mengembangkan perangkat pembelajaran IPS Terpadu, pada tahap Define, dilakukan analisis terhadap SK-KD yang berpotensi untuk dipadukan, selanjutnya semua SK-KD tersebut terpadu melalui tema. kemudian dilakukan pengembangan jaringan SK-KD. Pada tahap Design, dilakukan perancangan silabus dan RPP pembelajaran IPS Terpadu.Kata Kunci: Pengembangan Pembelajaran, dan Pembelajaran IPS Terpadu